Synthesis, characterization and post-modification of aromatic (Co)polyesters possessing pendant maleimide groups - Jadhav, Uday A.; Nagane, Samadhan S.; Wadgaonkar, Prakash P. (High Performance Polymers, 2023)
A new series of (co)polyesters possessing pendent maleimide groups was synthesized by low temperature solution polycondensation of 4, 4’-(5-maleimidopentane-2, 2-diyl) diphenol (BPA-MA) with isophthalic acid chloride (IPC), terephthalic acid chloride (TPC) and a mixture of TPC and IPC (50:50 mol %). Copolyesters were also synthesized by polycondensation of varying compositions of BPA-MA and bisphenol-A (BPA) with IPC. The chemical structures and compositions of (co)polyesters were confirmed by NMR spectroscopy. Inherent viscosity values and number-average molecular weights of (co)polyesters were in the range 0.50–0.76 dL/g and 17,700-32,100 g/mol, respectively, indicating the formation of reasonably high molecular weight polymers. (Co)polyesters were readily soluble in common organic solvents and could be cast into tough, transparent and flexible films from chloroform solutions. (Co)polyesters exhibited 10% weight loss and glass transition temperatures in the range 464–468 and 142–178°C, respectively. A representative copolyester possessing pendant maleimide groups was chemically modified via metal-free azide-maleimide 1,3-dipolar cycloaddition click reaction with two azido compounds, namely, (azidomethyl)benzene (Bz-N3) and 1-(azidomethyl)-pyrene (Py-N3) to yield corresponding modified copolyesters in a quantitative manner.